Measuring Driving-Related Attitudes Among Older Adults: Psychometric Evidence for the Decisional Balance Scale Across Time and Gender. (5th November 2015) - Sukhawathanakul, Paweena; Tuokko, Holly; Rhodes, Ryan E.; Marshall, Shawn C.; Charlton, Judith; Koppel, Sjaan; Gélinas, Isabelle; Naglie, Gary; Mazer, Barbara; Vrkljan, Brenda; Myers, Anita; Man-Son-Hing, Malcolm; et al.
Abstract: Purpose of the study: The Decisional Balance Scale (DBS) was developed to assess older adults' attitudes related to driving and includes both intrapersonal and interpersonal motivations for driving. This study examined the psychometric properties of the DBS ratings across 3 time points in a sample of 928 older drivers who participated in the Canadian Driving Research Initiative for Vehicular Safety in the Elderly (Candrive). Design and Methods: Measurement invariance of the DBS was assessed longitudinally and across gender. Results: Confirmatory factor analyses revealed that a two-factor model (positive and negative attitudes) for both driving beliefs related to the self and other provided a good fit to the data at each time point. Measurement invariance was supported across time and gender. Significant associations between the DBS factor scores and other driving measures (e.g., perceived driving ability and self-regulatory driving practices) provided evidence of convergent validity. Implications: The DBS appears to be a robust instrument for measuring attitudes toward driving and is recommended for continued use in future research on driving behaviors with older adults.